Perceptions of risk and predictive testing held by the first-degree relatives of patients with rheumatoid arthritis in England, Austria and Germany: a qualitative study - Stack, RJ; Stoffer, M; Englbrecht, M; Mosor, E; Falahee, M; Simons, G; Smolen, J; Schett, G; Buckley, CD; Kumar, K; Hansson, M; Hueber, A; et al. (BMJ Publishing Group, 2016)
Objectives The family members of patients with rheumatoid arthritis (RA) are at increased risk of developing RA and are potential candidates for predictive testing. This study explored the perceptions of first-degree relatives of people with RA about being at risk of RA and engaging in predictive testing. Methods # 34 first-degree relatives (siblings and offspring) of patients with RA from the UK, Germany and Austria participated in semistructured interviews about their perceptions of RA risk and the prospect of predictive testing. Interviews were audio-recorded, transcribed verbatim and analysed using thematic analysis. Results First-degree relatives were aware of their susceptibility to RA, but were unsure of the extent of their risk. When considering their future risk, some relatives were concerned about the potential impact that RA would have on their lives. Relatives were concerned that knowing their actual risk would increase their anxiety and would affect decisions about their future. Also, relatives were concerned about the levels of uncertainty associated with predictive testing. Those in favour of knowing their future risk felt that they would need additional support to understand the risk information and cope with the emotional impact of this information. Conclusions # Identifying individuals at risk of RA may allow targeted interventions to reduce the risk and consequence of future disease; however, relatives have concerns about predictive testing and risk information. The development of strategies to quantify and communicate risk needs to take these views into account and incorporate approaches to mitigate concerns and minimise the psychological impact of risk information.